Fundamental changes in the canonical contemplative life of nuns according to the apostolic constitution Vultum Dei quaerere and the instruction Cor orans - SZEWCZUL , BOŻENA (Prawo Kanoniczne, 2019)
Apostolic constitution of Pope Francis regarding women’s contemplative life Vultum Dei quaerere published on 29.06.2016, and executory instruction Cor orans published on 1.04.2018 by Congregation for Institutes of Consecrated Life and Societies of Apostolic Life implements series of changes for life of nuns of enclosure. It was necessary, because previous apostolic constitution Sponsa Christi regarding life of nuns, prepared by Pope Pius XII was published 66 zears ago on 21.1.1915. Long time period separating both constitutions causes, among other things, that changes implemented by new documents are far-reaching, and cause partial derogation of four canons Canon Law Codex of 1983 still in force, and complete abrogation of some previous, no-code judical norms regarding nuns. Newness (Novum) of the published documents, in the first place, is that all nun’s cloisters have an obligation of membership of the respective federation; description of the required conditions necessary for the cloister to receive real, and judiciary autonomy, and reasons of its loss; changes in institution of enclosure, and exlaustration of the nuns, as well as extention of initial nun’s formation, and implementation of additional, obligatory stages in it, that is aspirant’s, and postulate’s period. All above mentioned changes have been discussed in the article. Changes are proceded by recalling the definition of the canonical contemplation life, formulated bz Pope Pius XI in reminded above constitution Sponsa Christi, and mentioned by Pope Francis again in constitution Vultum Dei quaerere. This type of the article structure seemed to be necessary, in order to allow reader to make an evaluation of the changes in a life of nuns, and first of all to get an answer to a question: if the changes will more successfuly lead the nuns to interior contemplation? General historical, and statistical facts regarding the life of nuns were also included in the article.